Sexual Dimorphism of Cerebral Structural and Functional Changes in the Early Postresuscitative Period After Cardiac Arrest - A. V. Volkov; M. Sh. Avrushchenko; A. P. Barannik; R. Kh. Ziganshin; N. A. Gorenkova; Yu. V. Zarzhetsky (Общая реаниматология)
The investigation was undertaken to study early postresuscitative sexual differences in cerebral structural and functional changes 12 min after cardiac arrest in albino rats. There were great sexual differences in orientative-investigating behavior and anxiety before, as well as neurological recovering processes after clinical death, without distinctions in cardiopul-monary resuscitative processes and postresuscitative mortality. Common changes in the content of peptide substances having a molecular weight of as high as 5 kDa in the brain tissue and gender-associated features were revealed in the early postoperative period. The baseline increased behavioral activity and a rapid postresuscitative recovery of females, unlike males, are associated with the early postresuscitative development of neurodystrophic and degenerative changes in the neuronal populations of the hippocampus and cerebellum.